Budaya Kerja Kepolisian Dalam Pelayanan Masyarakat Di Polsek Anggeraja Kabupaten Enrekang - Wulan, Wulan; Mahsyar, Abdul; Yusuf, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of the research is to determine the work culture of the police in community service at the Anggeraja Police, Enrekang Regency. This type of research uses qualitative methods with a descriptive research type. Data collection techniques are through observation, interviews and documentation. The results of the research show that the Anggeraja Police Department's service to the community is said to be quite good, but there are several obstacles, namely regulations and the community's views on service and values. -Society's values are not fully implemented in accordance with the professional code of ethics. There are habits, rules and values as a reference for acting in solving problems. The Police Code of Ethics as a guideline for carrying out their duties cannot be said to be optimal when police officers are in the field in their assigned area. In reality, the police have not provided good services to the community because of favoritism and exclusion.